Food and Feed Additive of Insects: Economic and Environmental Impacts - Ojianwuna, Chioma Cynthia; Enwemiwe, Victor Ngozi; Esiwo, Eric; Orji, Gift Onyedikachi; Nkeze, Afamefune Januarius (International Journal of Child Health and Nutrition, 2023)
Background: Food insecurity and malnutrition in children may impose extreme disease conditions, which potentially affect the sustainability of zero hunger and wellness worldwide, leading to variations in nutritional patterns by region. Edible insects are common and are included in diets such as pastries, cookies, pasta, pies, flours, biscuits, candies, bars, chocolates, beverages, alcoholics, and so on. Methods: The current price of insect-incorporated foods and conventional foods in the grocery stores online were analyzed and compared. The architectural sketch of insect integrated rearing system. Edible insects can be reared to harvest or sourced from the wild, cleaned, steamed, and oven-heated before blending into fine powders for additives. The smooth powder is milled with other food ingredients before they are mixed thoroughly, pounded, baked, and cut into sizes. Results: The nutritional information of insect food and feed was higher than conventional products. Prices of all the conventional commodities were higher except for insect beverages (14.83≈11,274 nairas) and bars (22.30≈16,945 naira) (P<0.05). Marketable insect feed products are lacking, probably due to a lack of entrepreneurial intervention in this line of production. Conclusions: Considering the environment, insects have much more advantages. Foods of insects are quite cheap and encouraged in Asia-pacific than in the African region. The environmental, economic, and nutritional values of insects are equally an advantage over other animals. Modeling the price of edible insect foods is paramount to large-scale production. Concerted efforts and legislation are therefore required to promote this innovation in developing and under-developing nations.